Design of Novel Hydrogen-Bonding Donor Organocatalysts and Their Application to Asymmetric Direct Aldol Reaction - Akutsu, Hiroshi; Nakashima, Kosuke; Yanai, Hikaru; Kotani, Akira; Hirashima, Shin-ichi; Yamamoto, Tomoyuki; Takahashi, Ryuta; Yoshida, Akihiro; Koseki, Yuji; Hakamata, Hideki; Matsumoto, Takashi; Miura, Tsuyoshi (Synlett, 2017)
Asymmetric catalytic activities of various organocatalysts bearing double hydrogen-bonding donor units showing different pKa values were examined for direct aldol reactions of cyclohexanone with aromatic aldehydes. Organocatalyst with motif exhibiting the highest acidity resulted in the corresponding aldol products with the highest enantioselectivity. A good correlation has been observed between the asymmetric catalytic activity for direct aldol reactions and acidities of double hydrogen-bonding donating units.
Keywords: organocatalyst; direct aldol reaction; hydrogen-bonding donor; asymmetric reaction